Effects of two programs of exercise on body composition of adolescents with Down syndrome - Seron,Bruna Barboza (2014)
Objective: To investigate the effects of a 12 week aerobic and resistance exercise on body composition of adolescents with Down syndrome.Methods: A quasi-experimental study with 41 adolescents with Down syndrome, aged 15.5±2.7 years, divided into three groups: Aerobic Training Group (ATG; n=16), Resisted Training Group (RTG; n=15) and Control Group (CG; n=10). There were two types of training: aerobic, with intensity of 50-70% of the heart rate reserve 3 times/week, and resisted, with intensity of 12 maximum repetitions 2 times week. Both trainings were applied during a 12-week period. The percentage of fat evaluation was performed using plethysmography with Bod Pod(r)equipment. Waist circumference (WC), body weight and height were also measured. Paired t-test was used to compare variables before and after the exercise program.Results: The percentage of body fat did not change significantly for both groups that participated in the training intervention. However, CG showed a significant increase in this variable (31.3±7.2 versus 34.0±7.9). On the other hand, body mass index (BMI) and WC were significantly reduced for ATG (BMI: 27.0±4.4 and 26.5±4.2; WC: 87.3±11.1 and 86.2±9.7), while RTG and GC showed no differences in these variables.Conclusions: The aerobic and resisted training programs maintained body fat levels. ATG significantly reduced BMI and WC measures. Individuals who did not attend the training intervention increased their percentage of fat.